2023
DOI: 10.1007/s10857-023-09615-1
|View full text |Cite
|
Sign up to set email alerts
|

A promising approach to scaling up professional development: intelligent, interactive, virtual professional development with just-in-time feedback

Yasemin Copur-Gencturk,
Chandra Hawley Orrill

Abstract: The scalability and accessibility of quality professional development (PD) is an ongoing concern in the teacher education community, yet little research has been conducted on potential solutions. We aimed to address this gap by developing an interactive, virtual PD program that uses intelligent tutoring systems and provides instant feedback to teachers. We then explored the role of this program in developing teachers’ content and pedagogical content knowledge of mathematics. We collected data from 60 teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The theory of change posited in our program was that by improving teachers' content-specific knowledge (i.e., content knowledge [CK] and pedagogical content knowledge [PCK]), we could enhance the quality of mathematics instruction. We have reported in previous publications that teachers who completed the program improved their CK and PCK, as assessed by both locally developed and external measures (Copur-Gencturk & Orrill, 2023). We also explored the impact of the program on student outcomes through a randomized controlled trial and found that the mathematics performance of students whose teachers had completed the program was statistically higher than the mathematics performance of students whose teachers were in the control group (an effect size of 0.18; Copur-Gencturk et al, 2024).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The theory of change posited in our program was that by improving teachers' content-specific knowledge (i.e., content knowledge [CK] and pedagogical content knowledge [PCK]), we could enhance the quality of mathematics instruction. We have reported in previous publications that teachers who completed the program improved their CK and PCK, as assessed by both locally developed and external measures (Copur-Gencturk & Orrill, 2023). We also explored the impact of the program on student outcomes through a randomized controlled trial and found that the mathematics performance of students whose teachers had completed the program was statistically higher than the mathematics performance of students whose teachers were in the control group (an effect size of 0.18; Copur-Gencturk et al, 2024).…”
Section: Introductionmentioning
confidence: 94%
“…The program was developed over a 3-year period through an iterative process by gathering insights from experts and the targeted teacher population (i.e., middle school mathematics teachers; Copur-Gencturk & Orrill, 2023). Given that many students begin to fall behind in mathematics during the middle school years (National Assessment of Educational Progress [NAEP], 2022) and their mathematics achievement in middle school plays a critical role in their academic outcomes (e.g., Astin & Astin, 1992;Marsh et al, 2005; National Mathematics Advisory Panel [NMAP], 2008), we devoted our attention to a critical content area in the middle school curriculum: ratios and proportional relationships (e.g., Cai & Sun, 2002;Hoyles et al, 2001;Siegler et al, 2010;Thompson & Saldanha, 2003).…”
Section: The Current Study: the Developed Program And Its Content And...mentioning
confidence: 99%
See 1 more Smart Citation